The Effect of Text Organization Instruction on Students’ Expository Reading Comprehension - Siti Nurul Azisyah; Iskandar; Munir (International Journal of Language, Education, and Literature, 2026)
This study aims to investigate the effectiveness of text organization instruction in improving students’ expository reading comprehension, as well as to identify students’ challenges and explore teachers’ perceptions regarding its implementation. The research employed a sequential explanatory mixed-methods design, combining quantitative and qualitative approaches. The quantitative data were collected through pre-test and post-test to measure students’ reading comprehension before and after the intervention, while qualitative data were obtained through questionnaires and analysis of students’ responses to provide deeper insights into their experiences. The findings reveal that text organization instruction significantly improves students’ comprehension of expository texts. Students demonstrated better ability in identifying main ideas, recognizing supporting details, and understanding the relationships between ideas. In addition, the results indicate that well-organized texts reduce students’ difficulties in reading, as clear structures help them follow the flow of information more easily and minimize confusion.  Furthermore, students showed positive changes in motivation, confidence, and engagement in reading activities after receiving instruction on text organization. The integration of quantitative and qualitative findings confirms that text organization instruction is an effective pedagogical strategy for enhancing reading comprehension and supporting meaningful learning. Explicit teaching of text organization plays a crucial role in improving students’ ability to comprehend expository texts and should be considered an essential component in reading instruction.